2021
DOI: 10.2499/p15738coll2.134265
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting commodity prices using long-short-term memory neural networks

Abstract: This paper applies a recurrent neural network (RNN) method to forecast cotton and oil prices. We show how these new tools from machine learning, particularly Long-Short Term Memory (LSTM) models, complement traditional methods. Our results show that machine learning methods fit reasonably well the data but do not outperform systematically classical methods such as Autoregressive Integrated Moving Average (ARIMA) models in terms of out of sample forecasts. However, averaging the forecasts from the two type of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Such an observation has been found in other studies as well. Ly et al (2021) also noted in their study that the LSTM did not perform better than the traditional ARIMA model in single‐step ahead forecasting the cotton and oil prices. Also, in the study of Sun and Jin (2022), the ARIMA model achieved better results in 1‐h ahead to forecast the wind speed.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Such an observation has been found in other studies as well. Ly et al (2021) also noted in their study that the LSTM did not perform better than the traditional ARIMA model in single‐step ahead forecasting the cotton and oil prices. Also, in the study of Sun and Jin (2022), the ARIMA model achieved better results in 1‐h ahead to forecast the wind speed.…”
Section: Discussionmentioning
confidence: 92%
“…Multivariate variables are necessary to strengthen the performance of prediction models. Commonly used deep learning models include ANN (Ayankoya et al, 2016) and Long Short‐Term Memory (LSTM) (Ly et al, 2021; Rasheed et al, 2021). These models have good predictive power in single‐step forecasting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic comparison between traditional regression-based techniques and ML results showed that it was premature at the time to assume that the algorithms would outperform statistical methods. However, with improvements in mathematical modeling, data availability, and greater computing capacities, ML algorithms now yield satisfactory accuracy in some areas, even though regression-based techniques can still provide better results in specific contexts (Ly et al, 2021).…”
Section: Machine Learning and Traditional Regression Techniquesmentioning
confidence: 99%
“…As food is essential to people's day-to-day life, the accuracy in price prediction as well as knowing the prices in advance are indispensable to properly guide agricultural production, make a correct balance between supply and demand, increase farmer's income, assist the farmers to plan their next crop, and to help the government, farmers, business people in agriculture and consumers to get a clear market awareness, devising business plans, finetuning individuals own finances, and reducing the risks and uncertainties to be handled (Zhang et al, 2020). Though forecasting of agricultural price is pertinent and considered as paramount for many economic actors (Ly, Traore, & Dia, 2021), as literature confirms research has not reaped the benefits of deep learning-based agricultural price forecasting and remains to be an unsolved problem on date (Sagheer & Kotb, 2019;Paroissien, 2020).…”
Section: Introductionmentioning
confidence: 99%